Cap-Assisted Endoscopic Septotomy of Zenker's Diverticulum: Early and Long-Term Outcomes - Repici, Alessandro; Cappello, Annalisa; Spadaccini, Marco; Nicoletti, Rosangela; Carrara, Silvia; Fugazza, Alessandro; Galtieri, Piera Alessia; Lamonaca, Laura; Romana, Chiara; Badalamenti, Matteo; Di Leo, Milena; Pellegatta, Gaia; et al. (The American journal of gastroenterology, 2021)
Multiple therapeutic modalities including surgery and rigid and flexible endoscopy have been adopted to manage Zenker's diverticulum (ZD). Minimally invasive flexible endoscopic septotomy (FES) techniques have been increasingly favored over the past 20 years; however, long-term data are still scanty. The aim of this study is to evaluate early and long-term outcomes of FES for naive ZD in a single-center setting. From 2010 to 2017, ZD patients treated with FES were included in a prospectively maintained database (NCT03948438). Those who had already been treated surgically or endoscopically were excluded from the analysis. The Dakkak and Bennett dysphagia scale was used to rate the dysphagia. Persistent complete or near-complete resolution of symptoms (Dakkak and Bennett 0 or 1) was defined as clinical success. Postprocedural adverse events were reported according to ASGE lexicon. Overall, 256 consecutive patients were treated. Mean pouch size was 29.8 ± 11.3 mm. The procedure was successfully completed in all scheduled patients, with an early clinical success of 96.1%. Adverse events occurred in 3.5% (9/256) of patients. Eight of them were mild/moderate with no fatal events, whereas one patient required surgery. Recurrences occurred in 31.3% (80/256) of treated patients after a mean time of 9 ± 3 months and 95% of recurrences were treated by a second FES. At an average follow-up of 5.5 years, 95.3% of patients were asymptomatic after a mean number of 1.3 procedures. FES is a safe and effective treatment modality for patients with ZD. Recurrence rate is significant; however, endoscopic reintervention is associated with long-term relief of dysphagia.